The Effect of Creative Thinking and Innovative Behavior on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Bakrie Pasaman Plantations - Yulia Wulan Dhari; John Veri (Sean Institute, 2025)
This study aims to examine the influence of creative thinking and innovative behavior on employee performance, with job satisfaction as an intervening variable, at PT. Bakrie Pasaman Plantations. Data collection methods included a survey and questionnaire distribution, with a sample of 86 respondents. The analytical method used was path analysis using SmartPLS. The research results showed a significant influence of creative thinking and innovative behavior on job satisfaction. Creative thinking, innovative behavior, and job satisfaction significantly influence employee performance. Creative thinking significantly influences employee performance through job satisfaction. Innovative behavior also has an insignificant influence on employee performance through job satisfaction.